Current Treatment of Cleft Lip and Palate 2020
DOI: 10.5772/intechopen.89556
|View full text |Cite
|
Sign up to set email alerts
|

Orthognathic Surgery in Cleft Lip and Palate Patients

Abstract: Cleft lip and palate patients often exhibit severe dentofacial deformities that necessitate orthognathic surgery. Orthognathic surgery in these patients generally includes not only maxillary advancement, but also sagittal, horizontal, and vertical movement of both jaws. Surgical planning and execution presents many difficulties, caused by the presence of extensive scar tissues from previous surgeries, tissue deficiencies, the difficulty of aligning multiple segments of bone and soft tissues. Other challenges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The total airway amount in each cluster was long-drawn-out from prepubertal to post-pubertal intervals, but the cause for this concluding results withinside the branched association crooked into nowadays no elongated anteroposterior increase as withinside the case of the complete association, but in discrepancy, associated with perpendicular airway surge. Specifically in two-pronged cleft fatalities, significantly diminished guttural consonant airway echoing planetary in estimation to persons with out clefts twisted into as well showed in a CBCT learning [3].…”
Section: On Breathingmentioning
confidence: 80%
“…The total airway amount in each cluster was long-drawn-out from prepubertal to post-pubertal intervals, but the cause for this concluding results withinside the branched association crooked into nowadays no elongated anteroposterior increase as withinside the case of the complete association, but in discrepancy, associated with perpendicular airway surge. Specifically in two-pronged cleft fatalities, significantly diminished guttural consonant airway echoing planetary in estimation to persons with out clefts twisted into as well showed in a CBCT learning [3].…”
Section: On Breathingmentioning
confidence: 80%
“…Although most studies focused on horizontal maxillary stability, Park et al [63] reported that postoperative mandibular relapse in cleft patients had a strong positive correlation with mandibular clockwise rotation and setback amounts. Wong et al [64] could not find a significant difference between the relapse rates of individuals who received two surgical operations and those who received maxillary advancement surgery only. Some researchers used bone grafts to increase horizontal or vertical stability [61,63,64].…”
Section: Success Of Orthognathic Surgerymentioning
confidence: 88%
“…Wong et al [64] could not find a significant difference between the relapse rates of individuals who received two surgical operations and those who received maxillary advancement surgery only. Some researchers used bone grafts to increase horizontal or vertical stability [61,63,64]. It was reported that usage of grafts has a preventive effect on horizontal maxillary stability with an average of 1.72 mm less relapse [61].…”
Section: Success Of Orthognathic Surgerymentioning
confidence: 88%
See 1 more Smart Citation
“…10 However, in this case, the initial surgery aimed to setback the mandible to treat the cl III skeletal malformation in a CLP patient, a procedure that usually bears various dentofacial esthetic and functional problems, and does not address the hypoplasia in the midface. 11 Moreover, the complication that followed added a considerable adverse impact on the patient's condition, which necessitated prompt management.…”
Section: Discussionmentioning
confidence: 99%